2022
DOI: 10.1111/dme.14994
|View full text |Cite
|
Sign up to set email alerts
|

Overtreatment of older people with type 2 diabetes—a high impact frequent occurrence in need of a new definition

Abstract: Background Diabetes overtreatment is a frequent and major issue in older people with type 2 diabetes but its definition is often inconsistent and may be misleading. This critical review has aimed at examining the definitions of diabetes overtreatment in older people used in research studies. Methods Studies addressing diabetes overtreatment in people aged 65 or older were identified by searching the PubMed database according to an extensive search equation. Results Twenty‐two research studies providing a defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 44 publications
(104 reference statements)
0
8
0
1
Order By: Relevance
“…Avoiding overtreatment by GLT, either by prescribing appropriate GLT according to their individual risks-benefits balance or by deprescribing GLT, is therefore a key issue in the management of older patients, as recommended by various scientific societies these last years 2 . Nevertheless, there is currently no consensus on the definition of GLT overtreatment in older people 3 , which prevents a clear statement on which patients should undergo deprescribing of GLT. It is therefore worthwhile to define the profiles of patients for whom GLT should be deprescribed.…”
Section: To the Editormentioning
confidence: 99%
“…Avoiding overtreatment by GLT, either by prescribing appropriate GLT according to their individual risks-benefits balance or by deprescribing GLT, is therefore a key issue in the management of older patients, as recommended by various scientific societies these last years 2 . Nevertheless, there is currently no consensus on the definition of GLT overtreatment in older people 3 , which prevents a clear statement on which patients should undergo deprescribing of GLT. It is therefore worthwhile to define the profiles of patients for whom GLT should be deprescribed.…”
Section: To the Editormentioning
confidence: 99%
“…In this issue of Diabetic Medicine, we publish a review of the overtreatment of people with type 2 diabetes which highlights an absence of an agreed definition as well as suggesting a framework to develop a consensus definition based on a level of glycaemia that is inappropriate to the person's health with a high risk of adverse events from glucose-lowering treatments, especially hypoglycaemia. 2 This important work is key to establishing an evidence base to support safe prescribing and de-prescribing for ageing people living with type 2 diabetes.…”
Section: Through the Agesmentioning
confidence: 99%
“…Themes arising from that work included understanding how older people live with diabetes and how this may link to outcomes and service delivery; how non‐specialists healthcare professionals understand ageing with diabetes; lifestyle interventions to prevent frailty; technology use in ageing with diabetes; empowering self‐management and peer support for older people living with diabetes. In this issue of Diabetic Medicine, we publish a review of the overtreatment of people with type 2 diabetes which highlights an absence of an agreed definition as well as suggesting a framework to develop a consensus definition based on a level of glycaemia that is inappropriate to the person's health with a high risk of adverse events from glucose‐lowering treatments, especially hypoglycaemia 2 . This important work is key to establishing an evidence base to support safe prescribing and de‐prescribing for ageing people living with type 2 diabetes.…”
mentioning
confidence: 99%
“…To the editor, Christiaens et al have recently suggested in a Diabetic Medicine article that proposed definitions of diabetes overtreatment so far are not in agreement with each other. 1 They also pointed out that a standardized definition could be based on individualized hypoglycaemia risk and/or complications. In 22 articles they evaluated, the prevalence of overtreatment, based on glycated haemoglobin and antidiabetic drug use, ranged from 9.2% 2 to 79%, 3 depending on the age group, comorbidity burden and setting.…”
Section: E T T E R the Role Of Glycated Haemoglobin In Clinical Decis...mentioning
confidence: 99%
“…In 22 articles they evaluated, the prevalence of overtreatment, based on glycated haemoglobin and antidiabetic drug use, ranged from 9.2% 2 to 79%, 3 depending on the age group, comorbidity burden and setting. 1 Overtreatment has been widely considered an issue of older age. When glycated haemoglobin is taken into account, it may be of marginal importance among subjects aged younger than 60 years.…”
Section: E T T E R the Role Of Glycated Haemoglobin In Clinical Decis...mentioning
confidence: 99%